1997
DOI: 10.1007/s002040050384
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of CI-924 on hepatic peroxisome proliferation, microsomal enzyme induction, PCNA, and apoptosis in B6C3F1 mice and Wistar rats

Abstract: The lipid lowering agent 5,5'[[1,1'-biphenyl]-2,5-diylbis(oxy)]bis[2,2-dimethylpentanoic acid] (CI-924) is a peroxisome proliferator in rats and mice, but increased the incidence of hepatic tumors in mice only. Male and female B6C3F1 mice and albino Wistar rats were treated with CI-924 at doses of 0, 25 and 75 mg/kg for 1, 3, 7 and 28 days. Our aim was to identify species differences potentially related to tumorigenicity and to establish the time course of early events related to or associated with peroxisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Roberts et al (1995) demonstrated that the basal frequency of apoptosis in rat liver was 0.030%, and that after 10 days of treatment of rats with the peroxisome proliferator nafenopin, the frequency of apoptosis had decreased to 0.002%. Another peroxisome proliferator, the drug CI-924, decreased the frequency of apoptosis in rat liver after 7 and 28 days (from 0.66 to 0.41% and 1.47 to 0.32%, respectively) but not mouse liver, even though other responses (peroxisomal enzyme induction and hepatocyte proliferation) were similar in both species (Hofstra et al, 1997). Surprisingly, few studies have evaluated this effect of peroxisome proliferators on apoptosis in vivo, although there are many reports of this response to peroxisome proliferators in cultured hepatocytes in vitro.…”
Section: Apoptosis Modulation By Peroxisomementioning
confidence: 96%
See 1 more Smart Citation
“…For example, Roberts et al (1995) demonstrated that the basal frequency of apoptosis in rat liver was 0.030%, and that after 10 days of treatment of rats with the peroxisome proliferator nafenopin, the frequency of apoptosis had decreased to 0.002%. Another peroxisome proliferator, the drug CI-924, decreased the frequency of apoptosis in rat liver after 7 and 28 days (from 0.66 to 0.41% and 1.47 to 0.32%, respectively) but not mouse liver, even though other responses (peroxisomal enzyme induction and hepatocyte proliferation) were similar in both species (Hofstra et al, 1997). Surprisingly, few studies have evaluated this effect of peroxisome proliferators on apoptosis in vivo, although there are many reports of this response to peroxisome proliferators in cultured hepatocytes in vitro.…”
Section: Apoptosis Modulation By Peroxisomementioning
confidence: 96%
“…To date, there are no published studies extending these in vitro findings to the in vivo situation, i.e., investigation of modulation of apoptosis in livers of PPAR␣ knockout mice following in vivo treatment. As discussed above, only one published study evaluated the effect of a peroxisome proliferator on apoptosis in wild type mice, with no effect of treatment observed (Hofstra et al, 1997).…”
Section: Mechanismsmentioning
confidence: 99%